Understanding an Excellence Financial Strategy using Feasibility Study Towards FNB Startup: A Case Study of SYFO - Wijayanto, Kevin Nurizky; Irawan, Atika (Proceedings International Conference on Education Innovation and Social Science, 2023)
SYFO is an emerging company in the food and beverage sector that offers households and career women throughout Indonesia with SYFOin, a ready-to-cook product that simplifies their daily culinary activities. Prior to implementing a go-to-market strategy, a financial feasibility study was necessary. This study employed quantitative methodology, acquiring primary data from SYFOin and secondary data from industry peers. This investigation's feasibility study was evaluated employing Payback Period, Net Present Value (NPV), and Internal Rate of Return (IRR), along with scenario evaluation, in order to assess and reduce the business's financial risks. The SYFO feasibility analysis consisted of three scenarios: the most probable, the pessimistic, and the optimistic. The findings of the financial feasibility analyze indicate that SYFO is financially viable as a FnB startup company with a payback period of 2.54 years achieved before the end of the project life (5 years), with a favorable total NPV of IDR 892,696,221 and an IRR value of 42.06%, which is greater than the pessimistic and optimistic scenarios.